Analysing Auto ML Model for Credit Card Fraud Detection (International Journal of Innovative Research in Computer Science & Technology, 2021)
Fraud Detection is a major concern these  days because of digitalization. We are totally dependent on  online transactions these days for even very small needs.  There is no doubt that online transactions have made our  life very easy but it has increased risk on other hand. And  this risk can be very harmful one day. Confidential data is  being stolen by the different apps and it is sold in  international market. Which later on comes to us in totally  different and very harmful way. So why not to use  technology again to stop these risks and flaws. Various ML  techniques has been observed by researchers but Auto ML  is yet not discovered on a wider platform. Therefore, this  paper at first aims to explore the trending technology Auto  ML. Then a model for evaluating Auto ML is suggested and  analysed with different classification algorithms. The  experimental results ascertained the accuracy of Auto ML followed by a comparative analysis of ML and Auto ML.
Keywords: Auto ML; Classification; Credit card; Fraud detection; Machine learning